Irradiation-Induced Changes in the Immunogenicity of Lung Cancer Cell Lines: Based on Comparison of X-rays and Carbon Ions - Ran, Juntao; Wang, Jiangtao; Dai, Ziying; Miao, Yandong; Gan, Jian; Zhao, Chengpeng; Guan, Quanlin (Frontiers in Public Health, 2021)
Increasing the immunogenicity of tumors is considered to be an effective means to improve the synergistic immune effect of radiotherapy. Carbon ions have become ideal radiation for combined immunotherapy due to their particular radiobiological advantages. However, the difference in time and dose of immunogenic changes induced by Carbon ions and X-rays has not yet been fully clarified. To further explore the immunogenicity differences between carbon ions and X-rays induced by radiation in different “time windows” and “dose windows.” In this study, we used principal component analysis (PCA) to screen out the marker genes from the single-cell RNA-sequencing (scRNA-seq) of CD8+ T cells and constructed a protein-protein interaction (PPI) network. Also, ELISA was used to test the exposure levels of HMGB1, IL-10, and TGF-β under different “time windows” and “dose windows” of irradiation with X-rays and carbon ions for A549, H520, and Lewis Lung Carcinoma (LLC) cell lines. The results demonstrated that different marker genes were involved in different processes of immune effect. HMGB1 was significantly enriched in the activated state, while the immunosuppressive factors TGF-β and IL-10 were mainly enriched in the non-functional state. Both X-rays and Carbon ions promoted the exposure of HMGB1, IL-10, and TGF-β in a time-dependent manner. X-rays but not Carbon ions increased the HMGB1 exposure level in a dose-dependent manner. Besides, compared with X-rays, carbon ions increased the exposure of HMGB1 while relatively reduced the exposure levels of immunosuppressive factors IL-10 and TGF-β. Therefore, we speculate that Carbon ions may be more advantageous than conventional X-rays in inducing immune effects.